Efficacy of preoperative pulmonary rehabilitation in lung cancer patients: a systematic review and meta-analysis of randomized controlled trials - Yalun Guo; Mengdie Pan; Meidi Xiong; Miao Liu; Na Zhu; Haoxu Dong; Chunhua Zhang (Discover Oncology)
Abstract Although previous studies have shown that preoperative pulmonary rehabilitation training may improve postoperative prognosis in patients with lung cancer, the literature included in the existing meta-analysis is highly heterogeneous and lacks effective subgroup analysis. Therefore, an updated meta-analysis is needed to integrate the latest published randomized controlled clinical trials (RCT). This updated analysis was performed to identify the clinical effects of preoperative pulmonary rehabilitation on physical rehabilitation (lung function, activity endurance, and dyspnea), psychological rehabilitation, quality of life, length of hospital stay, and postoperative pulmonary complications in patients with lung cancer. The PubMed, Embase, Cochrane Library, and Web of Science database were searched since inception up to March 2024. A random-effects model was used to pool data, and sensitivity and subgroup analyses were performed to explore the stability of outcomes and potential sources of heterogeneity. All analyses were conducted via Review Manager 5.4.1 and STATA 15.0. The final analysis included 11 RCTs with 1250 patients. The results of meta-analysis suggest that preoperative pulmonary rehabilitation can significantly improve the quality of life of patients with lung cancer after surgery (SMD: 0.16; 95% CI: 0.01, 0.32; P = 0.04) and significantly reduce the risk of postoperative pulmonary complications (PPCs) (RR: 0.39; 95% CI: 0.25, 0.60; P < 0.0001). The results of subgroup analysis suggested that the effect of combined preoperative and postoperative rehabilitation was significantly better than that of preoperative rehabilitation alone, and the effect of short-term preoperative pulmonary rehabilitation (≤ 3 weeks) was significantly better than that of long-term rehabilitation. Preoperative pulmonary rehabilitation for patients with lung cancer can significantly improve their postoperative quality of life and reduce postoperative complications, but factors such as intervention time and intervention method may affect the rehabilitation effect.